Resilience and Leadership Agility in Times of Crisis: Lessons Learned from Amnt Site Batu Hijau Mining Indonesia - Galuh Yudha Satriya; Pande Made Kutanegara; Ambar Teguh Sulistyani (Journal of World Science, 2025)
Given the unprecedented global economic and operational disruptions caused by the COVID-19 pandemic, which led to significant declines across various industries, particularly the mining sector, a critical question emerges regarding the effective strategies companies employed to ensure their survival and continuity. This study investigates how Amman Mineral Nusantara (AMNT) successfully navigated the unprecedented challenges of the COVID-19 pandemic, focusing on the critical role of agile leadership. Utilizing a qualitative research approach with in-depth interviews and documentation from AMNT's Batu Hijau site, the study examines the interplay of agile leadership, strategic commitment, integrated risk management, and market adaptation. Findings reveal that AMNT's resilience stemmed from its adaptive and transformative leadership, which fostered a culture of rapid response, uncertainty management, and robust communication and collaboration. The company's commitment to human resources and ESG principles, alongside comprehensive risk management and crisis-driven innovation, enabled sustained operational continuity, financial stability, and employee welfare. Key determinants of agile leadership effectiveness—individual responsibility, trust, self-organized teams, pioneer spirit, and focus—were crucial in navigating the crisis and promoting organizational resilience, particularly within the Indonesian work culture. This research highlights agile leadership as a vital model for effective crisis management and a catalyst for long-term organizational transformation and growth.